Reclamability Classification and Nature of Ravines of Chambal Commanded Area - Seth, S.P.; Bhatnagar, R.K.; Chauhan, S.s. (Journal of Soil and Water Conservation, 2022)
Nearly 21% of Chambal commanded area is 4inproductive on account ofgood lands having been converted into ravines (Mehta 1958) due to erosion of water. Since the back flooding. action of river water which was responsiblej , for deepening and wideaing of gullies have been minimised to certain extent by the installation of dams on river Chambal, the reclamation of ravines for agriculture and forestry use may be feasible.